Morphofunctional aspects of restorative processes in the optic nerve after traumatic injury under the influence of high doses of corticosteroids - N.M. Moiseenko (Ukrainian Society of Ophthalmologists, 2015)
Search of conditions conducive to the activation of regenerative processes and restoration of the functions of the optic nerve after traumatic injuries is relevant. The purpose of this research was to study morphological and functional aspects of the rehabilitation process in the optic nerve after traumatic injury under the influence of high doses of corticosteroids. Material and methods. 24 adult rabbits were used,12 of them were from the group of rabbits injured without treatment and another 12 were treated with methylprednisolone on the second day after the injury. Morphological study was conducted on the 14th day, and the functional one (the amplitude of pupillary reaction) was carried out on the 14th day and in 1 month. Results After the use of high doses of corticosteroids in the intracranial portion of the optic nerve, on the 24th day, improvement of microcirculation, decreasing swelling and remyelination of nerve fibers were detected. At the same time, the amplitude of the pupillary reaction has increased in one month. Conclusions. It was established that in case of traumatic injury, usage of high-dose corticosteroids contributes not only to morphological but also to functional signs of activation of regenerative processes of the optic nerve.